The development of small molecule inhibitors of the essential Leishmania bromodomain LdBDF5 - Carter, JL (2023)
The leishmaniases are a collection of neglected tropical diseases caused by Leishmania parasites that are epidemic across Africa, Asia, and Latin America. Leishmania have complex lifecycles, adopting a range of phenotypes to survive in multiple hosts. Epigenetic processes link genotype to phenotypic diversity in a population and play a crucial role in regulation of the Leishmania lifecycle. Targeting the epigenetic mechanisms may therefore be a promising strategy for the treatment of leishmaniasis. Bromodomain-containing proteins (BCPs) are epigenetic proteins that recognise acetylated lysine (KAc) residues in histones and regulate transcription. LdBDF5 is a BCP that contains two bromodomains (LdBDF5.1 and LdBDF5.2) and interprets histone acetylation marks in Leishmania to maintain normal levels of gene expression. Inducible gene deletion has shown that BDF5 in Leishmania is essential for parasite survival in its two main lifecycle stages: the promastigote and the amastigote, demonstrating it as a suitable target for the disruption of epigenetic processes. The work in this dissertation describes the development of high affinity, potent, and selective ligands that have enabled chemical validation of LdBDF5 as a target for antileishmanial drug discovery. A fragment-based screening approach was adopted to identify ligands for LdBDF5. A range of KAc-mimicking fragments were synthesised and evaluated using biophysical assays. Compound 18 was identified as a hit with a Kd value of 1410 ± 84 nM (microscale thermophoresis) for LdBDF5.1. Analogues of 18 were synthesised with modifications at two positions (N-1 and C-2 of the benzimidazole) to probe the structure-activity relationship (SAR) of LdBDF5.1 (Figure 0.1). The highest affinity compounds resulted from modifications at the C-2 position with an ethyl linker functionalised with 3 cyano 4 methylbenzene. The binding mode of these compounds was confirmed using X ray crystallography with compound 181 complexed to LmxBDF5.1. The 3 cyano 4 methylbenzene on the C-2 ethylene forms effective π-stacking interactions with Y96, enabling the nitrile to form a key hydrogen bonding interaction with the T99 hydroxyl in the binding site of LdBDF5.1. Compounds designed to target LdBDF5.1 were tested in cell viability assays and exhibited growth inhibition of the Leishmania promastigotes, supporting the genetic studies that demonstrated the essentiality of BDF5 for promastigote viability. Five compounds showed increased activity (EC50 values of 0.41–1.72 µM) relative to the clinically approved anti-leishmanial miltefosine (EC50 = 1.79 µM). It was also demonstrated that the compounds have >100 fold selectivity for LdBDF5.1 over the human BRD4(1) and CREBBP bromodomains. This work provides a foundation for the future exploration of BDF5 inhibitors in antileishmanial drug discovery.